High Disease Activity May Increase Fear-Avoidance Beliefs in Rheumatoid Arthritis - Mehmet Engin TEZCAN; Berfu CİNKİT DOĞAN and Nesrin ŞEN and Mehmet SARGIN (Archives of Rheumatology, 2017)
Objectives: This study aims to compare fear-avoidance (FA) beliefs of rheumatoid arthritis (RA) patients with osteoarthritis (OA) of hand patients and fibromyalgia (FM) patients and evaluate its relationship with RA activity and duration. Patients and methods: The study included 206 patients with RA (34 males, 172 females; mean age 49 years; range 20 to 72 years), 57 patients with FM (57 females; mean age 48 years; range 20 to 71 years), and 50 patients with OA of hand (4 males, 46 females; mean age 43 years; range 43 to 77 years). FA beliefs were assessed with modified Fear-Avoidance Belief Questionnaire (mFABQ). RA patients were dichotomized according to disease activity and disease duration separately; cutoff values were disease activity score 28 of 3.2 and six months of disease activity, respectively. Results: Modified Fear-Avoidance Belief Questionnaire scores were similar in patients with RA, OA of hand, and FM. RA patients in non-remission group had higher mFABQ scores. Moreover, mFABQ scores were similar in RA patients with early and established disease groups. Conclusion: Fear-avoidance beliefs of patients with RA were similar with OA of hand patients and FM patients. However, higher disease activity in RA was related with escalated FA beliefs. Further studies focusing on pathophysiology of FA beliefs in patients with RA are warranted for effective pain management of RA.